2009
DOI: 10.1007/s00702-009-0202-4
|View full text |Cite
|
Sign up to set email alerts
|

Auricular vagus somatosensory evoked potentials in vascular dementia

Abstract: A new method for the assessment of vagus nerve function has recently been introduced into clinical practice. In the present study we could show that, contrary to our results in Alzheimer's disease (AD), in patients with vascular dementia (VaD) vagus sensory evoked potentials (VSEP) did not show statistically significant differences as compared to healthy controls. Thus, we hypothesize that the new method of VSEP could possibly contribute to a differential diagnosis between early cases of AD and VaD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 34 publications
0
16
1
Order By: Relevance
“…Subsequent work focused on VSEP latencies, as prolonged latencies may be indicative of a reduced myelination of the vagus nerve and a concomitant reduced conduction velocity of the nerve fibers. Prolonged latencies of the VSEPs after tVNS have been documented in elderly (Fallgatter et al, 2005) and people suffering from mild cognitive impairments and Alzheimer's disease (Polak et al, 2014(Polak et al, , 2007, but not in people with vascular dementia (Polak et al, 2009), Parkinson's disease (Weise et al, 2015) or major depression (Polak et al, 2014). Yet, it is not always the full spectrum of P1-N1-P2 potentials that is delayed after tVNS.…”
Section: Somatosensory Evoked Potentialsmentioning
confidence: 99%
“…Subsequent work focused on VSEP latencies, as prolonged latencies may be indicative of a reduced myelination of the vagus nerve and a concomitant reduced conduction velocity of the nerve fibers. Prolonged latencies of the VSEPs after tVNS have been documented in elderly (Fallgatter et al, 2005) and people suffering from mild cognitive impairments and Alzheimer's disease (Polak et al, 2014(Polak et al, , 2007, but not in people with vascular dementia (Polak et al, 2009), Parkinson's disease (Weise et al, 2015) or major depression (Polak et al, 2014). Yet, it is not always the full spectrum of P1-N1-P2 potentials that is delayed after tVNS.…”
Section: Somatosensory Evoked Potentialsmentioning
confidence: 99%
“…ABVN-SEP potentials occur at millisecond latencies similar to early auditory evoked potentials (AEP), indicating that they may originate from brainstem vagal nuclei [ 9 ]. Patients with Alzheimer’s disease (AD) showed prolonged latencies [ 13 ], whereas patients with vascular dementia did not [ 12 ]. These results are in line with degeneration of the vagal nuclei complex in the course of AD [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Sixthly, 3 of the AD patients and 2 of the MCI subjects had (mild to moderate) vascular lesions as revealed by an MRI or CT examination, which is no rare finding even in healthy elderly. A former study [28] showed a normal latency of VSEP in patients with vascular dementia. Although increasing age often means increasing microangiopathic lesions (without fulfilling the imaging criteria of vascular dementia), especially since MRI scanners with higher magnetic fields generate images with higher resolution, a confounding factor in the present study cannot be excluded.…”
Section: Discussionmentioning
confidence: 88%
“…This somatosensory potential is characterized by prolonged latencies with increasing age [26]. In addition, neurodegenerative processes such as AD have been found to further increase the latency of the potential, which -in contrast -could not be demonstrated for patients with cerebrovascular diseases [27,28].…”
Section: Fg Metzger and T Polak Contributed Equally To This Workmentioning
confidence: 97%